Relationship Between Locus Of Control, Paranormal Beliefs, And Magical Ideation Among Young Adults Of Pakistan - Rozia Malik; Shammem Akhtar; Fatima Ali Raza Mughal (Journal of Rawalpindi Medical College)
Objective: Para normality, often seen as violating fundamental scientific principles, includes beliefs in phenomena such as spirits, extrasensory perception, and fortune telling. These extraordinary beliefs are linked to belief. Locus of control (LOC), which refers to an individual's perception of control as internal or external, is a well-studied concept. This study aimed to explore the relationship between locus of control, paranormal beliefs, and magical ideation in early adulthood, and to examine how individual differences affect these variables.